Spatiotemporal Variations of Freezing and Thawing Indices During the Past Four Decades in Tibet - Liao, Ying; Li, Yiying; Fan, Jihui; Galoie, Majid; Motamedi, Artemis (Frontiers in Ecology and Evolution, 2021)
Freezing and thawing indices (FI and TI) are commonly used indicators for assessing of climate changes and estimation of permafrost extent in cold regions. The Tibetan Plateau encompasses the wide areas of frozen soil and ice-covered regions in China. Nevertheless, due to a lack of accurate regional-scale data sets, previous researches for estimation of permafrost extent on the Tibetan Plateau using FI and TI are rare or with less-accuracy. In this study, FI and TI and their spatiotemporal variations from 1978 to 2017 on the Tibetan Plateau were calculated, mapped and analyzed using daily temperature obtained from 34 meteorological stations. The results showed that, during the past four decades, the mean annual of FI and TI of the Tibetan Plateau are 1241.36 ℃·day and 1290.22 ℃·day respectively. Both temporal and spatial variations of FI and TI are negatively correlated with significant downward and upward trends for FI and TI respectively, but the changing rates vary in different regions. The spatial distribution of FI showed that from southeast to northwest of the Tibetan Plateau, it was increased and for TI is in reverse. Also, FI in high altitudes decrease more obviously than in low altitudes, but for TI, is in reverse. Based on the high-resolution calculation of FI and TI, the current permafrost area was estimated about 0.59×106 km2, which was compared with the estimated extent in 1978 and the extent from published map in 2017, providing some implications for permafrost degradation assessment and engineering construction over the Tibetan Plateau.